Effects of Parental Involvement Via Fitness Application on Psychosocial Factors among Overweight and Obese Adolescents in China: A Pilot Study - Hai, Tianjiao; Kim, Vincent Wee Eng; Mai, Yiqiang (Advances in Social Sciences Research Journal, 2026)
Background: The rising prevalence of overweight and obesity among adolescents poses significant public health challenges, with notable psychosocial consequences such as reduced self-esteem, self-efficacy, and social identity. Parental involvement is recognized as a key factor influencing adolescent health behaviors, yet evidence on technology-mediated family interventions remains limited, particularly in urban Chinese contexts. Objective: This pilot study aimed to examine the effects of a parental involvement fitness application (PIFA) intervention on psychosocial outcomes—self-esteem (SES), self-efficacy (SEF), and social identity (SI)—among overweight and obese adolescents in China. Methods: A two-week cluster-randomized controlled trial was conducted with 28 junior high school students (aged 12–15) in Jiaozuo City, Henan Province. Participants were randomized at the school level into two groups: the PIFA group (parent-child co-activity via fitness app) and the Individual Fitness App (IFA) group. Psychosocial outcomes were assessed using validated scales at baseline and post-intervention. Data were analyzed using generalized estimating equations (GEE) and effect size calculations. Results: The PIFA group showed significantly greater improvements in SES and SEF compared to the IFA group, with large effect sizes (SES: d=0.85; SEF: d=1.23). Significant group-by-time interactions were observed for both outcomes (p<0.001). Although both groups demonstrated improvements in SI, between-group differences did not reach statistical significance (p=0.085), with moderate effect sizes observed in the PIFA group (d=0.56). Conclusion: Parental involvement through a fitness application appears to enhance self-esteem and self-efficacy among overweight and obese adolescents more effectively than individual app use alone. The findings underscore the value of integrating family-based, technology-supported strategies into adolescent obesity interventions. Future studies should address limitations related to sample size, measurement methods, and intervention duration to further validate and optimize such approaches.